NLRC3 is a potential prognostic biomarker that is correlated with immune cell infiltration in lung adenocarcinoma - Yingchen Zhuo; Xueqian Li; Weiyi Feng (Scientific Reports, 2023)
Abstract The NLR family CARD domain containing 3 (NLRC3) gene has been reported to have a crucial effect on immunity, inflammation, and tumorigenesis. However, the clinical relevance of NLRC3 in lung adenocarcinoma (LUAD) remains unclear. This study analyzed both RNA sequencing data and corresponding clinical outcomes obtained from public databases to identify (i) NLRC3 as a tumor suppressor in LUAD and (ii) its predictive value for the likelihood of patient responsiveness to immunotherapy. The results showed that NLRC3 expression was reduced in LUAD and was lower in advanced-stage tumors. Additionally, reduced NLRC3 expression was correlated with worse patient prognosis. The protein level of NLRC3 was also observed to have prognostic significance. Moreover, downregulation of NLRC3 was found to suppress the chemotaxis and infiltration of antitumor lymphocyte subpopulations as well as natural killer cells. Mechanistic analysis indicated that NLRC3 may be involved in immune infiltration by regulating chemokines and their receptors in LUAD. Furthermore, NLRC3 functions as a molecular switch in macrophages, whereby it mediates the polarization of M1 macrophages. Patients with high NLRC3 expression were also found to exhibit a more promising response to immunotherapy. In conclusion, NLRC3 could serve as a potential prognostic biomarker for LUAD, help predict the immunotherapeutic response of patients, and guide personalized strategies for the treatment of LUAD.